2012
DOI: 10.1007/s10043-012-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanism of ultrasonic fluorescence modulation in light scattering medium based on diffusion approximation with varying refractive index

Abstract: In this study, we propose a model to describe the mechanism of ultrasonic fluorescence modulation based on the application of a modified diffusion approximation, which is derived from the radiative transfer equation with consideration of the varying refractive index. The model was evaluated by computation with finite element method (FEM) to simulate the physical phenomena of our previous experiments. The simulation shows that the measured power of the modulated fluorescence signal at the boundary of 40-mm-thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Here the normalised ultrasound modulated signal is shown to investigate the trend with concentration which was found to vary with the concentration linearly. This linear relationship of modulated signal with source concentration is consistent with the expression (18) derived in [27]. It should also be noted that in [28] the US modulated fluorescence signal was observed to only increase when the fluorophore concentration is low and it will decrease in the high concentration region.…”
Section: Modulation Depthsupporting
confidence: 89%
“…Here the normalised ultrasound modulated signal is shown to investigate the trend with concentration which was found to vary with the concentration linearly. This linear relationship of modulated signal with source concentration is consistent with the expression (18) derived in [27]. It should also be noted that in [28] the US modulated fluorescence signal was observed to only increase when the fluorophore concentration is low and it will decrease in the high concentration region.…”
Section: Modulation Depthsupporting
confidence: 89%
“…The realization of this, however, is hampered by factors such as high optical scattering, absorption, and autofluorescence that collectively (2 of 12) 1602895 www.small-journal.com US level spatial resolution can be achieved. [4] One such hybrid approach is US modulated fluorescence tomography (USMFT) [5][6][7][8] which produces fluorescent emission modulated at the US frequency from excited fluorescent probes within the US focal zone. Despite gains in spatial resolution this technique produces extremely low modulated light levels (modulation depth 10 −6 -10 −4 [9] ).…”
Section: Introductionmentioning
confidence: 99%
“…This work describes the preparation and characterization of nanoscale liposomes containing lipids labeled with the carbocyanine dyes DiIC18(5) (1,1′-dioctadecyl-3,3,3′,3′tetramethylindodicarbocyanine, 4-chlorobenzenesulfonate salt) ("DiD," Life Technologies Ltd, CA, USA) and DiIC18 (7) (1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbocyanine Iodide) ("DiR," Life Technologies Ltd, CA, USA). Experimentally the emission spectra from liposomes labeled at a range of different concentrations and ratios of DiD to DiR in their equilibrium state are obtained to identify the effect the increase in concentration and hence proximity has on fluorescence emission and quenching.…”
Section: Introductionmentioning
confidence: 99%
“…For low concentrations modulation of local fluorophore density was proposed, while quenching effects were suspected to dominate at higher concentrations . Duc et al further added modulation of the excitation intensity of the pump beam by refractive index changes as an additional contribution to the induced concentration variation . However, modulation of the excitation intensity infers a quadratic behavior of UMF with increasing ultrasound pressure, while Yuan et al reported a linear relationship. , Yuan et al hypothesized that the cause of UMF differs between fluorescence in a clear liquid medium and a scattering medium .…”
Section: Introductionmentioning
confidence: 99%